Post-operative ventilatory nursing regime of research coronary artery bypass graft patients - H Potgieter; H Uys; W E Nel (AOSIS, 1999)
The nurse working in the intensive care unit functions as an independent practitioner under the Nursing Act and arising SANC regulations. Opsomming Die doel van hierdie navorsing is om die invloed van 'n pre-operatiewe bloedgasanalise op die post-operatiewe ventilatoriese verplegingsregime van 'n koronere vatomleidingspasient te bepaal. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.